Schlieren photography on freely flying hawkmoth - Liu, Yun (Biol Lett, 2018)
The aerodynamic force on flying insects results from the vortical flow structures that vary both spatially and temporally throughout flight. Due to these complexities and the inherent difficulties in studying flying insects in a natural setting, a complete picture of the vortical flow has been difficult to obtain experimentally. In this paper, Schlieren, a widely used technique for highspeed flow visualization, was adapted to capture the vortex structures around freely flying hawkmoth (Manduca). Flow features such as leading-edge vortex, trailing-edge vortex, as well as the full vortex system in the wake were visualized directly. Quantification of the flow from the Schlieren images was then obtained by applying a physics-based optical flow method, extending the potential applications of the method to further studies of flying insects.